Current Success and Efficiency of Autologous Ovarian Transplantation: A Meta-Analysis. (August 2017) - Pacheco, Fernanda; Oktay, Kutluk
Context: Ovarian cryopreservation followed by autotransplantation is still considered an experimental strategy for fertility preservation (FP) mainly because the success rates are unknown. Objective: To determine cohort epidemiologic characteristics and success rates of autologous ovarian tissue transplantation (OTT) with previously cryopreserved tissue. Materials and Methods: Literature review from 1999 to October 1, 2016. Additional cases were retrieved from meeting abstracts and own database. We selected studies that reported autologous OTT with previously banked tissue in humans. We did not include any cases involving fresh ovarian tissue transplantation or those performed to treat idiopathic premature ovarian failure/insufficiency. Both authors reviewed and selected studies for eligibility, which resulted in 59 full-text studies assessed for eligibility. Cases were extracted from original reports and reviews by the junior author, and the senior author reviewed and verified the extracted data. Results: Nineteen reports were included for qualitative synthesis. In 10 studies, detailed data were available to determine clinical and live birth + ongoing (LB + OG) pregnancy as well as endocrine restoration rates. Three hundred nine OTTs were performed with cryopreserved tissue, resulting in the birth of 84 children and 8 OG pregnancies. The cumulative clinical and LB + OG rates were 57.5% and 37.7%, respectively, and the endocrine restoration rate was 63.9%. Conclusion: Success rates with cryopreserved OTT have reached promising levels. Given these recent data, ovarian tissue cryopreservation should be considered as a viable option for FP.